Carbon monoxide yields of cigarettes and their relation to nicotine yield and type of filter. Issue 5975 (12th July 1975) - Russell, M A; Cole, P V; Idle, M S; Adams, L
Abstract : Carbon monoxide (CO) yields of 11 popular brands of British cigarette, two types of cigarette containing tobacco-substitute, and one brand of cigar were measured under standardized conditions. Yields of the conventional cigarettes ranged from 5.0 to 20.2 mg per cigarette (1.3 to 4.7% by volume). The cigar yielded 81.7 mg (10.0%) CO and the two semi-synthetic cigarettes 17.2 (4.2%) and 28.2 mg (6.2%) CO. Puff-by-puff analysis showed an increase in CO concentration as a cigarette is smoked. In brands with nicotine yields over 1.0 mg no relationship was apparent between nicotine yield and CO yield, and the filters of cigarettes in this category did not appear to reduce the CO yield. In the low nicotine cigarettes with ventilated filters there appeared to be some correlation between nicotine yield and CO yield, and these filters were highly effective in reducing CO yield, owing mainly to the ventilation. We suggest that official publication of CO yields might motivate manufacturers to produce cigarettes with lower yields.